Sex worker womenand the vulnerabilityt to the HIV/aids - Borba, Kátia P; Clapis, Maria José (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: considering problems in working with women so-called sex professionals in Guarapuava-Paraná, this study heads us for understanding theirexposure to HIV/aids, through determined dimensions in health promotion at individual and collective levels. Objective: to identify programming, social andindividual factors involving vulnerability to HIV/aids in female sex professionals; verify personal difficulties faced by these women infected by HIV and theirprofessional position to make decision about measures taken to prevent HIV/aids. Methods: qualitative approach research having life topic story as itsinstrument to collect data; discussion on data has been made through analyses of contents, according to Bardin. Conclusion: we have reached the conclusionthat programming, social and individual factors make people more vulnerable to HIV/aids. Although many women are aware of having HIV and despites widedistribution of information, it is difficult to change habits in a social and cultural environment which had facilitated the infection. The work with HIV/aidsprevention cannot be restricted to the distribution of information by making people aware of the problem, moreover, the work with cultural predisposition andits limits for protected practice.